Effects of Aqueous Artichoke (Cynara scolymus) Leaf Extract on Hepatic Damage Generated by Alpha-Amanitine - Kaymaz, Mustafa Bahadir; Kandemir, Fatih Mehmet; Pamukcu, Esra; Eroksuz, Yesari; Ozdemir, Necmi (Kafkas Univ, Veteriner Fakultesi Dergisi, 2017)
Approximately 90% of mushroom poisoning deaths in the world is caused by types of Amanita phalloides. Alpha-amanitine has a bicyclic octapeptide structure, which is the main structure responsible for these poisoning cases. In the present study, it was aimed to investigate effects of leaf extracts with artichoke extract on this toxicity. In the study, 28 male rats of Sprague-Dawley species were randomized to 4 groups. The groups were designed as control; receiving serum physiological solution of 0.1 mL intraperitoneally (ip), alpha-amanitine; receiving 3 mg/kg single dose ip, artichoke leaf extract; receiving 1.5 g/kg orally for 14 d, and treatment group, receiving alpha-amanitine 3 mg/kg single dose ip+artichoke leaf extract 1.5 g/kg orally for 14 d. It was determined that alpha-amanitine increased hepatic malondialdehyde (MDA) levels, and decrease superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), catalase (CAT) activities with decreasing glutathione (GSH) levels. The supplementation with extract with artichoke, decreased MDA levels, it improved antioxidant parameters, and histopathological findings, so it was decided that extract with artichoke juice might be beneficial in alpha-amanitine related hepatic damage.
Alfa-amanitin ıle oluşturulmuş karaciğer hasari üzerine enginar (Cynara scolymus) sulu yaprak ekstresinin etkileri
Keywords: Artichoke; Alpha-Amanitine; Amanita phalloides; Antioxidant; Hepatotoxicity